O estudo da congruência semântica em questões de equação de 1º grau nas avaliações de aprendizagem em processo - Garcia, Gladys Beatriz Churata (2019)
This work aims to contribute with research involving large scale research, especially the In-Process Learning Assessment (AAP). With regard to the analysis of this type of document, we present implications of the content of equation of the first degree and linear systems of two equations of the first degree with two variables, from the perspective of the registers of semiotic representation. For the theoretical and methodological course of the research we formulate the following research question: what is the incidence of the criteria of semantic congruence in questions containing first degree equations? The methodological course of this research was qualitative in the documentary modality. In bibliographical terms, our main reference was the contributions of Raymond Duval's theory. In the documentary perspective we present the analysis of the second volume of the Teacher's Book for the 8th year of Elementary School, as well as the analysis of eight questions extracted from AAP editions applied in the period from 2012 to 2018. The results of our research revealed signs in the form necessary attention to the vocabulary appropriate to the algebraic context, as well as the possibility of minimizing non-conserved congruence criteria.